2017
DOI: 10.1002/jso.24653
|View full text |Cite
|
Sign up to set email alerts
|

“Heat shock protein 70 in pancreatic diseases: Friend or foe”

Abstract: The heat shock response in pancreatitis that is activated via HSP70 protects acinar cells through multiple simultaneous mechanisms. It inhibits trypsinogen activation and modulates NF-κB signaling to limit acinar cell injury. On the other hand, HSP70 is overexpressed in pancreatic cancer and is hijacked by the cellular machinery to inhibit apoptosis. Inhibition of HSP70 in pancreatic cancer by a novel compound, Minnelide, has shown considerable clinical promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 82 publications
0
33
0
Order By: Relevance
“…The water-soluble pro-drug of triptolide, Minnelide, was recently reported to show promising activity in patients with gastrointestinal malignancies in Phase I clinical trial 21,22 . Multiple mechanisms underlying TPL-induced antitumor activity have been described in the literature including inhibition of NFκB, c-Myc, HSP70 [23][24][25][26][27][28][29][30] , and XPB (ERCC3) 31 . Among them, inhibition of the ATPase activity of the XPB subunit of the transcription factor complex TFIIH is supported by biochemical evidence, which shows direct covalent binding of triptolide to XPB 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble pro-drug of triptolide, Minnelide, was recently reported to show promising activity in patients with gastrointestinal malignancies in Phase I clinical trial 21,22 . Multiple mechanisms underlying TPL-induced antitumor activity have been described in the literature including inhibition of NFκB, c-Myc, HSP70 [23][24][25][26][27][28][29][30] , and XPB (ERCC3) 31 . Among them, inhibition of the ATPase activity of the XPB subunit of the transcription factor complex TFIIH is supported by biochemical evidence, which shows direct covalent binding of triptolide to XPB 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we treated acinar cells from C mice with KRIBB11and found that HSF1 inhibition accelerated the death/necrosis and structural collapse of acinar cells (Additional le 1: Fig. S2C), which suggested that the core role of HSF1/HSPs on the protection of pancreas in stress condition [24]. Next, we treated acinar cells from KC mice with KRIBB11 and found that HSF1 inhibition suppressed the formation of ductal-like spheres, in other words, KRIBB11 inhibited the pancreatic cancer tumorigenesis in vitro (Additional le 1: Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Driven by the KRAS oncogene mutation caused abnormal activation of multiple pathways (mainly on Ras-MAPK and PI3K-AKT-mTOR pathways [30]), the homeostasis of acinar cells was remolding [6] and the phenotype of pancreatic acinar cells gradually transforms from acinar cells to ductal-like cells (acinar cells undergo ADM); in this process, the transcriptome of acinar cells changed (the loss of acinar markers amylase and the gain of ductal markers CK19) [31]. Mentionable, HSF1/HSPs are important for the maintenance of the proteostasis of cells (including normal pancreatic acinar cells) in various stress condition and protect them against the damage of PTSs such as pancreatitis [24]. In this study, we found that EGFR-HSF1 axis was important for Kras oncogene mutation induced abnormal MAPK pathway activation driven PTSs and pancreatic cancer tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…All these imply that Hsp70 members play an important role in cancer. Previous studies indicate that Hsp70A1A is involved in pancreatic cancer and hepatocellular carcinoma [32,33], but the relationship between Hsp70A1B and tumor progression and the mechanism which involved in is still not well defined. Our previous research found that Single cell RNA sequencing of T cells confirmed that HspA1B was up regulated in activated CD8+ T and Treg cells and represses CD8+ T cell functions in vitro.…”
Section: Introductionmentioning
confidence: 99%